PERTANGGUNG JAWABAN NOTARIS ATAS PEMBUATAN AKTA PERUBAHAN ANGGARAN DASAR DAN PERUBAHAN SUSUNAN PENGURUS YAYASAN YANG MENGANDUNG CACAT HUKUM (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NO. 1873.K/PDT/2012) - DWI AZMAWI ARDHAWINSYAH (PREMISE LAW JURNAL, 2017)
A Notary is a public official who has the authority to draw up authentic deeds and the other authorities as it is stipulated in Article 1868 of the Civil Code. A foundation as a legal entity is established by using a notarial authentic deed. Therefore, a Notary plays an important role in the establishment and the authorization of a foundation as a legal entity. The research used juridical normative method. It also used descriptive analytic method. The result of the research showed that the regulation on making a deed on the amendment of statutes and the structure of foundation management according to Law No. 16/2001 in conjunction with Law No. 28/2004 on Foundation states that the amendment can be done according to the decision of the patron’s meeting which is presented by 2/3 of them. The Panel of Judges’ consideration and the analysis on the legal consideration in the Supreme Court’s Ruling No. 1873 K/Pdt/2012 is that the revocation of the notarial deed No. 2/2004 on November 3, 2004 made by Notary/PAAT ST as the defendant III is in accordance with legal provision because the making of the deed is illegal and legally defective. Keywords: Notary’s Liability, Foundation Deed, Legally Defective